Newcastle disease: A review - Dyary, Hiewa Othman; Husseiun, Rozita Saadi (Sulaimani Journal for Pure and Applied Sciences, 2024)
Newcastle disease (ND) is a contagious disease caused by infection with the Newcastle disease virus (NDV), a member of the genus Orthoavulavirus (family Paramyxoviridae). Chickens are the primary infected species, although most domestic and wild birds are susceptible. The disease is endemic in Asia, the Middle East, Africa, and Central and South America, causing significant economic losses in the infected farms through reduced egg production, reduced weight gain, and mortalities. The NDV genome is a negative-sense, single-stranded RNA genome of about 15,190 nucleotides and encodes six structural and two nonstructural proteins. Velogenic NDVs are highly virulent and may cause up to 90% mortalities, while mesogenic strains cause depression, weight loss, reduced egg production, and mortalities around 10%. Infection mainly occurs through inhaling or consuming virus aerosols or contaminated dust. ND is endemic in many parts of Iraq and poses a significant threat to the poultry industry. Immunization is the most common practice to protect chickens in endemic areas. Some compounds were reported to have antiviral activities against the virus in embryonated chicken eggs; however, there is no approved treatment for ND. This review discusses the etiology, epidemiology, replication cycle, pathogenicity, economic impact, and diagnosis of ND, as well as the prevention and control of the disease in poultry.
Keywords: Newcastle disease virus; velogenic; replication cycle; Newcastle disease; vaccination